2001
DOI: 10.1076/jcen.23.4.502.1224
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Priming in Parkinsons Disease: Evidence for Delayed Spreading Activation

Abstract: Nineteen persons with Parkinson's disease (PD) and 19 matched control participants completed a battery of online lexical decision tasks designed to isolate the automatic and attentional aspects of semantic activation within the semantic priming paradigm. Results highlighted key processing abnormalities in PD. Specifically, persons with PD exhibited a delayed time course of semantic activation. In addition, results suggest that experimental participants were unable to implicitly process prime information and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
54
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 0 publications
9
54
1
1
Order By: Relevance
“…This result is consistent with findings of delayed lexical-semantic activation during semantic priming in some patients with PD (Angwin et al, 2005;Arnott et al, 2001;Grossman et al, 2002). Also worthy of note, Kotz, Frisch, Von Cramon, and Friederici (2003) found that patients with a basal ganglia lesion demonstrated an Table 5.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This result is consistent with findings of delayed lexical-semantic activation during semantic priming in some patients with PD (Angwin et al, 2005;Arnott et al, 2001;Grossman et al, 2002). Also worthy of note, Kotz, Frisch, Von Cramon, and Friederici (2003) found that patients with a basal ganglia lesion demonstrated an Table 5.…”
supporting
confidence: 78%
“…Impairments to semantic processing have also been identified in PD (Bocanegra et al, 2015;Lewis, Lapointe, Murdoch, & Chenery, 1998;Portin, Laatu, Revonsuo, & Rinne, 2000), including deficits to semantic inhibition (Arnott et al, 2010;Copland, Sefe, Ashley, Hudson, & Chenery, 2009) and alterations to automatic or controlled semantic priming (Angwin, Chenery, Copland, Murdoch, & Silburn, 2005Angwin et al, 2009;Arnott, Chenery, Murdoch, & Silburn, 2001;Arnott et al, 2011;Copland, 2003;Grossman et al, 2002). Thus, developing a better understanding of the nature and extent of semantic impairments in PD is critical to understanding language function and cognitive decline in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the current data add to mounting evidence that various aspects of language processing are indeed compromised in PD, including semantic priming (e.g., Arnott et al, 2001), lexical ambiguity resolution in sentences (Copland et al, 2000a(Copland et al, , 2001 and sentence processing (Grossman, 1999). The same pattern of priming for NS and PD groups is also at odds with the view that language disturbances following NS lesions are due to white matter pathway disruption causing corticocortical or thalamocortical disconnection (Alexander et al, 1987).…”
contrasting
confidence: 48%
“…This may also reveal insight into the impairments exhibited by some patient populations (Arnott et al, 2001). In order to understand these complex behaviors, one must first begin to understand how these manipulations affect brain regions associated with language processing.…”
Section: Introductionmentioning
confidence: 99%